Потенциал загрязнения атмосферы на территории Республики Казахстан по данным реанализа ERA5 за 2021 год - Saspugayeva, G.Y.; Aktayeva, G.S.; Zhaken, A.M.; Duzbayeva, N.M.; Zandybai А.; Daribay A.О. (Fundamental and Experimental Biology, 2024)
According to the data of the reanalysis of ERA5, the potential of atmospheric pollution in the boundary layer of the atmosphere was calculated and the nature of its distribution over the territory of the Republic of Kazakhstan was described, the areas of the greatest and least repeatability of the conditions for the formation of the potential of atmospheric pollution were identified. As a result of human economic activity, a large number of pollutants appears in the atmosphere, the most significant changes in the quality of atmospheric air are observed in large cities. At the moment, the self-cleaning mechanism cannot cope with a large number of pollutants in the atmosphere, which leads to the formation of high concentrations of impurities. The potential of atmospheric pollution is one of the widely used ways to assess the self-purification of the atmosphere from pollutants. This method represents the ratio of average concentrations of harmful substances with actual emissions in a specific and conditional region.